Food insecurity in Cape Town: how inadequate access affects human health and livelihoods - Anthony, Jonathan A (Department of Political Studies, 2015)
Despite the increase in research on urban food insecurity, little has explicitly focused on spatial food access and malnutrition and under-nutrition amongst the urban poor in South Africa. Therefore, using a quantitative household data survey completed by the African Food Security Urban Network in 2008, this study examines the relationship of spatial food access and malnutrition and under-nutrition in three areas of Cape Town's peri-urban areas: Ocean View, Philippi, and Khayelitsha. An analysis of the survey data yields significant relationships between supermarkets and dietary diversity, as well as a robust relationship between poor household food access and malnutrition and under-nutrition. This study examined the differences of dietary diversity between Ocean View, Philippi, and Khayelitsha. This research discovered that while Ocean View had the highest household dietary diversity scores, they were also the most vulnerable to fluctuations due to their lack of spatial access to supermarkets. This study is a departure point for future research on these critical aspects of urban food insecurity in South Africa.